2014
DOI: 10.1016/j.bios.2014.06.062
|View full text |Cite
|
Sign up to set email alerts
|

Evanescent wave DNA-aptamer biosensor based on long period gratings for the specific recognition of E. coli outer membrane proteins

Abstract: An evanescent wave fiber optic sensor for detection of Escherichia coli (E. coli) outer membranes proteins (EcOMPs) using long period gratings (LPGs) as a refractometric platform is presented. The sensing probes were attained by the functionalization of LPGs inscribed in single mode fiber using two different methods of immobilization; electrostatic assembly and covalent binding. The resulting label-free configuration enabled the specific recognition of EcOMPs in water by monitoring the resonance wavelength shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Later, Queirós et al [83] reported an LPG functionalized with aptamers for the detection of E. Coli outer proteins with a LOD of 1 nM.…”
Section: Biosensorsmentioning
confidence: 99%
“…Later, Queirós et al [83] reported an LPG functionalized with aptamers for the detection of E. Coli outer proteins with a LOD of 1 nM.…”
Section: Biosensorsmentioning
confidence: 99%
“…Not only antibodies but also nucleic acids, such as oligonucleotidic probes (DNA) [8,52], peptide nucleic acid probes (PNA) [53][54][55], and aptamers [34,35,56,57], have been also coupled to OFGs for the detection of different targets, consisting of short oligonucleotides, genomic DNA, and even proteins or small molecules (Table 2). Finally, a series of other BREs, based on biointeractions such as enzymatic processes [58,59], biotin/streptavidin affinity [18,33,[60][61][62], virus-specific recognition (bacteriophage T4/Escherichia coli bacteria) [63][64][65][66] and biomimetic affinity processes with molecularly imprinted polymers (MIPs) [67], have been implemented (Table 3).…”
Section: Applicationsmentioning
confidence: 99%
“…Beyond imaging, optical fibres have also been used extensively for sensing purposes. Optical fibre sensors have been explored for a wide range of applications including sensing of temperature [31][32][33], pressure [33,34], enzyme activity [35,36], presence of nucleic acids [36,37], pH [38,39], and oxygen saturation [38]. Detailed reviews can be found elsewhere [33,34,36,[40][41][42].…”
Section: Optical Fibres: From Telecommunications To Biomedical Imaginmentioning
confidence: 99%